ONLINE RELATIONSHIP MARKETING TERHADAP CUSTOMER LOYALTY BERDASARKAN PERSPEKTIF TEORI SINYAL (SIGNALING THEORY) - B1021161018, Wenseslaus Tanwira (Jurnal Manajemen Update, 2020)
The purpose of this study was to determine the effect of ORM on customer loyalty which was examined from the perspective of the signaling theory that occurs in the banking sector. Signaling theory is used to see the tendency of companies to build relationships with consumers by sending signals to consumers through a variety of dissemination of internet tools and applications to communicate transparency, security, and privacy to influence consumer perceptions, behavior, and interests. Data were analyzed by quantitative methods with the SEM-PLS method with 384 samples. The results of this study indicate that ORM activities such as engagement and interactivity have a significant direct effect on customer loyalty and online trust. Online trust in this study has a significant effect on customer loyalty and has a partial mediating role.Keywords: engagement, interactivity, online trust, customer loyaltyReferensiAhn, T., Hong, M. & Pedersen, P.M. (2014). Effects of perceived interactivity and web organization on user attitudes. European Sport Management Quarterly. 14. 111-128.Anderson, R. & Srinivasan, S. (2003). E-satisfaction and e-loyalty: a contingency framework. Psychology and Marketing. 20. 123-138.Benlian, A. & Hess, T. (2011), â€œThe signalling role of it features in influencing trust and participation in online communitiesâ€, International Journal of Electronic Commerce, 15, 7-56.Bleier, A. and Eisenbeiss, M. (2015), â€œThe importance of trust for personalized online advertisingâ€, Journal of Retailing, 91, 390-409.Brodie, R.J., Ilic, A., Juric, B. & Hollebeek, L. (2013), â€œConsumer engagement in a virtual brand community: an exploratory analysisâ€, Journal of Business Research, 66, 105-114.Brun, I., Durif, F. & Ricard, L. (2014), â€œE-relationship marketing: a cognitive mapping introspection in the banking sectorâ€, European Journal of Marketing, 48, 572-594.Brun, I., Rajaobelina, L. & Ricard, L. (2014), â€œOnline relationship quality: scale development and initial testingâ€, International Journal of Bank Marketing, 32, 5-27.Casalo, L.V., FlaviÃ¡n, C. & GiunalÃu, M. (2007), â€œThe influence of satisfaction, perceived reputation and trust on a consumerâ€™s commitment to a websiteâ€, Journal of Marketing Communications, 13, 1-17.Chen, K. & Yen, D.C. (2004), â€œImproving the quality of online presence through interactivityâ€, Information and Management, 42, 217-226.Ching, H.L. & Ellis, P. (2006), â€œDoes relationship marketing exist in cyberspace?â€, Management International Review, 46, 557-572.Cobos, L., Wang, Y.C. & Okumus, F. (2009), â€œAssessing the web-based destination marketing activities: a relationship marketing perspectiveâ€, Journal of Hospitality Marketing and Management, 18, 421-444.Colgate, M., Buchanan-Oliver, M. & Elmsly, R. (2005), â€œRelationship benefits in an internet environmentâ€, Managing Service Quality, 15, 426-436.Etemad-Sajadi, R. (2016), â€œThe impact of online real-time interactivity on patronage intention: the use of avatarsâ€, Computers in Human Behaviour, 61, 227-232.Fang, Y. H. (2012), â€œDoes online interactivity matter? Exploring the role of interactivity strategies in consumer decision makingâ€, Computers in Human Behaviour, 28, 1790-1804.Farquhar, J. & Rowley, J. (2006), â€œRelationships and online consumer communitiesâ€, Business Process Management Journal, 12, 162-179.Gan, L., Sim, C.J., Tan, H.L. & Tna, J. (2007), â€œOnline relationship marketing by Singapore hotel websitesâ€, Journal of Travel and Tourism Marketing, 20, 1-19.Geiger, S. & Martin, S. (1999), â€œThe internet as a relationship marketing tool â€“ some evidence from Irish companiesâ€, Irish Marketing Review, 12, 24-36.Guo, M. (2014), â€œRelationship marketing in an online social media context: newspaper versus television brand websites comparisonâ€, Journal of Media Business Studies, 11, 1-26.Hallowell, R. (1996), â€œThe relationships of customer satisfaction, customer loyalty, and profitability: an empirical studyâ€, International Journal of Service Industry Management, 7, 27-42.Harker, M. J. (1999), â€œRelationship marketing defined. An examination of current relationship marketing definitionsâ€, Marketing Intelligence and Planning, 17, 13-20.Howcroft, B., Durkin, M., Armstrong, G. & Emerson, E. (2007), â€œSmall business-bank relationshipsand the role of internet bankingâ€, The Service Industries Journal, 27, 947-961Jeon, H., Jang, J. & Barrett, E.B. (2016), â€œLinking website interactivity to consumer behavioural intention in an online travel community: the mediating role of utilitarian value and online trustâ€, Journal of Quality Assurance in Hospitality &Tourism, 18, 1-24.Kabadayi, S. & Price, K. (2014), â€œConsumer-brand engagement on Facebook: liking and commenting behavioursâ€, Journal of Research in Interactive Marketing, 8, 203-223.Kandampully, J., Zhang, T.C. & Bilgihan, A. (2015), â€œCustomer loyalty: a review and future directions with a special focus on the hospitality industryâ€, International Journal of Contemporary Hospitality Management, 27, 379-414.Kamran-Disfani, O., Mantrala, M.K., Izquierdo-Yusta, A. & MartÃnez-Ruiz, M.P. (2017), â€œInteraction, engagement, and perceived interactivity in single-handed interactionâ€, Journal of Business Research, 77, 14-22.Kirmani, A. & Rao, A.R. (2000), â€œNo pain, no gain: a critical review of the literature on signaling unobservable product qualityâ€, Journal of Marketing, 64, 66-79.Mavlanova, T., Benbunan-Fich, R. & Koufaris, M. (2012), â€œSignalling theory and information asymmetry in online commerceâ€, Information & Management, 49, 240-247.Mishra, K.E. & Li, C. (2008), â€œRelationship marketing in fortune 500 US and Chinese web sitesâ€,Journal of Relationship Marketing, 7, 29-43.Mollen, A. & Wilson, H. (2010), â€œEngagement, telepresence and interactivity in online consumer experience: reconciling scholastic and managerial perspectivesâ€, Journal of Business Research, 63, 919-925.Morgan, R.M. & Hunt, S.D. (1994), â€œThe Commitment-Trust theory of relationship marketingâ€, Journal of Marketing, 58, 20-38.Pan, Y., Sheng, S. & Xie, F.T. (2012), â€œAntecedents of customer loyalty: an empirical synthesis and re-examinationâ€, Journal of Retailing and Consumer Services, 19, 150-158.Pengnate, S. F. & Sarathy, R. (2017), â€œAn experimental investigation of the influence of website emotional design features on trust in unfamiliar online vendorsâ€, Computers in Human Behaviour, 67, 49-60.Prentice, C. & Loureiro, S.M.C. (2017), â€œAn asymmetrical approach to understanding configurations of customer loyalty in the airline industryâ€, Journal of Retailing and Consumer Services, 38, 96-107.Sashi, C. M. (2012), â€œCustomer engagement, buyer-seller relationships, and social mediaâ€, Management Decision, 50, 253-272.Shapiro, J. M., Romano, N.C. & Mittal, B. (2004), â€œEmergent internet technology applications for relationship marketingâ€, Journal of Relationship Marketing, 2, 85-108.Shin, D., Choi, M., Kim, J.H. & Lee, J. (2016), â€œInteraction, engagement and perceived interactivity in single-handed interactionâ€, Internet Research, 26, 1134-1157.Siregar, S. 2013. Metode penelitian kuantitatif. Jakarta : PT Fajar Interpratama Mandiri.Solihin, M. & Dwi, R. 2013. â€œAnalisis SEM-PLS dengan WarpPLS.3.0â€. Yogyakarta: Penerbit Andi.Srinivasan, S.S., Anderson, R. & Ponnavolu, K. (2002), â€œCustomer loyalty in e-commerce: an exploration of its antecedents and consequencesâ€, Journal of Retailing, 78, 41-50.Taj, S.A. (2016), â€œApplication of signalling theory in management research: Addressing major gaps in theoryâ€, European Management Journal, 34, 338-348.Thakur, R. (2016), â€œUnderstanding customer engagement and loyalty: a case of mobile devices for shoppingâ€, Journal of Retailing and Consumer Services, 32, 151-163.Vivek, S.D., Beatty, S.E. & Morgan, R.M. (2012), â€œConsumer engagement: exploring customer relationships beyond purchaseâ€, Marketing Theory and Practice, 20, 122-146.Wang, L., Law, R., Guillet, B.D., Hung, K. & Fong, K.C. (2015), â€œImpact of hotel website quality on online booking intentions: eTrust as a mediatorâ€, International Journal of Hospitality Management, 47, 108-115.Xu, Q. & Sundar, S.S. (2014), â€œLights, camera, music, interactionâ€, Communication Research, 41, 282-308.Yoo, C.W., Kim, Y.J. & Sanders, G.L. (2015), â€œThe impact of interactivity of electronic word of mouth systems and e-Quality on decision support in the context of the e-marketplaceâ€, Information & Management, 52, 496-505.Zineldin, M. (2000), â€œBeyond relationship marketing: technologicalship marketingâ€, Marketing Intelligence and Planning, 18, 9-23.